Compaction of granular columns under thermal cycling - Luo Yuxuan; Lu Haiyang; Ai Xinyu; Liu Zelin; Yuan Houfei; Ge Zhuan; Zeng Zhikun; Wang Yujie (National Science Open, 2025)
Granular materials undergo compaction under periodic temperature fluctuations, leading to various engineering and geological phenomena from landslides to silo compaction. Although thermal effects on granular materials have been extensively studied in soil mechanics and geology, the underlying physical mechanisms remain unclear. This study investigates the compaction dynamics of granular materials subjected to thermal cycling using monodisperse glass beads and polydisperse sand packings. We demonstrate that differential thermal expansion between the container and the grains drives compaction through shear. We quantify compaction dynamics using three established fitting models: Kohlrausch-Williams-Watts (KWW), double-exponential, and logarithmic functions. Our results reveal that granular materials exhibit slow relaxation processes in response to weak perturbations, displaying aging dynamics similar to those observed in glassy systems. These findings provide insights into fundamental mechanisms of granular compaction with broad implications for geological and engineering applications.